Analysis of World-Scale Mitochondrial DNA Reveals the Origin and Migration Route of East Asia Goats - Peng, Weifeng; Zhang, Yiyuan; Gao, Lei; Feng, Cailing; Yang, Yujiao; Li, Bingyi; Wu, Lili; Wu, Ali; Wang, Shuping; Ren, Xue; Chen, Zehui; Zhang, Min; et al. (Frontiers in Genetics, 2022)
Despite much attention on history of goat evolution, containing its origin, demographic history and expansion route, remains controversial. To address these questions, we collected 4189 published goat DNA sequences including 1228 sequences from 57 breeds of China, and 2961 sequences from other 71 countries, and carried out integrated analysis. We found goat breeds from South China have the highest genetic diversity of lineage B, and subclades B2 only were found in Southwest China, suggesting that lineage B (particularly, subclade B2) probably originated from Southwest China and its surrounding areas. In addition, in this study, we found that lineage A from South China also present higher genetic diversity and earlier expansion time (10, 606 years ago), even earlier than breeds from Middle East. Hence, we speculated that South China and surrounding areas not only was the origin area of lineage B, but also was an important“transportation hub” for lineage A spreading to North China and Southwest Asia. Furthermore, according to analysis of correlation between genetic differentiation value λ1 and λ2 and geographical distance, we further confirmed that two phases of migration in goat breeds of North China. These results will contribute to a better understanding of the origin and migration history of domestic goat.